Adaptive acceleration in growth and development of salamander hatchlings in cannibalistic situations. (20th November 2014) - Kishida, Osamu; Tezuka, Ayumi; Ikeda, Akiko; Takatsu, Kunio; Michimae, Hirofumi; Moore, Ignacio
Summary In most animal species, the hatchling stage is a highly vulnerable life‐history stage. In many fish and amphibian species, hatchling abundance varies substantially among sites and years, with the result that selection strength in conspecific interactions such as cannibalism is also variable. The variability of selection leads species to evolve phenotypic plasticity, and adaptive trait changes in hatchlings that depend on the density of conspecifics can therefore be expected. However, plasticity strategies in response to cannibalistic interactions in this vulnerable life‐history stage have received little attention. Because cannibalism success is dependent on the size balance between predator capturing organ and prey body, and also on the prey‐capturing ability of the cannibal and the escape ability of its prey, we hypothesize that hatchlings will exhibit faster growth and development in response to conspecific interactions. We performed a series of experiments to test this hypothesis, using pre‐feeding larvae of a cannibalistic salamander (Hynobius retardatus). Many traits of the hatchlings reared with conspecifics were larger than the same traits in those reared alone, because the former hatchlings grew faster and were more advanced developmentally. The time to the beginning of feeding was shorter, and swimming speed as an indicator of escape performance was faster, for hatchlings reared with conspecifics. Hatchlings reared with conspecifics more successfully cannibalized small hatchlings and were also highly resistant to being cannibalized by large conspecifics, compared with hatchlings reared alone. These differences in cannibalism success and avoidance of cannibalization were well explained by differences in gape and head size, respectively, between the interacting hatchlings. Therefore, acceleration of growth and development of hatchlings in the proximate presence of conspecifics may confer significant fitness advantages on hatchlings in a high‐density cannibalistic situation. Developmental and growth plasticity may thus be a powerful adaptive mechanism that allows individuals to respond to the dynamic character of salamander populations in nature.